Programa bolsa famÃlia: dimensÃo e efeito sobre a pobreza na regiÃo nordeste - Francisco Sharle de Sales (2010)
The Northeast region is known for being one of the regions that more has poor and miserable people in Brazil. This way, this region is also one that most needs public social policies to combat poverty and misery in this country. Within this context, emerged the importance of a study of the Bolsa-FamÃlia Program (PBF), transference of income program from the Federal Government to that region. Specifically referring to the study of the PBF in this work, it looked for to highlight the real dimension of the PBF in the Northeast and the effect on poverty and misery that this program has brought to that region. That is, the study aimed to determine and analyze the size of the Bolsa FamÃlia and its effect on poverty / extreme poverty in Brazilian Northeast. For this purpose, they were utilized the tabular and graphical analysis and argumentative descriptive analysis. Indicators were also used to show the way of calculating the targeting indicators (coverage and under-coverage) of the PBF and the indicators of poverty and misery found on the websites of the institutions surveyed. The results showed that, being a region with many social inequalities, the Northeast region of Brazil is one that most receive benefits from PBF since the beginning of this, justifying, thus, the program. Concerning the effect of the PBF on poverty and extreme poverty in the Northeast, it was observed, with few exceptions, that there were reductions in the number of poor and indigent people in rural and urban areas. Related to intensity and severity of poverty / extreme poverty, the reductions werenât so significant in general.